2011
DOI: 10.1016/j.ijid.2011.01.011
|View full text |Cite
|
Sign up to set email alerts
|

Galactomannan-guided preemptive vs. empirical antifungals in the persistently febrile neutropenic patient: a prospective randomized study

Abstract: A preemptive approach may reduce empirical antifungal use without compromising survival in persistently febrile neutropenic patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
49
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(50 citation statements)
references
References 29 publications
0
49
0
1
Order By: Relevance
“…Invasive fungal infections (IFIs) are an important complication in immunocompromised individuals, particularly in neutropenic patients with hematological malignancies 1 . Over the last decades, this group of patients has presented severe infections, which has been the cause of high mortality rate 2,3 .…”
Section: Introductionmentioning
confidence: 99%
“…Invasive fungal infections (IFIs) are an important complication in immunocompromised individuals, particularly in neutropenic patients with hematological malignancies 1 . Over the last decades, this group of patients has presented severe infections, which has been the cause of high mortality rate 2,3 .…”
Section: Introductionmentioning
confidence: 99%
“…To date, several studies have been compared the cost-effectiveness of different antifungals used in the EAT approach in patients with PFN (15,(27)(28)(29)(30). However, although new approaches have been proposed for the management of this syndrome (8,11,31), none of these studies compared the cost-effectiveness of these new approaches to the standard approach of EAT.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, Tan et al in a study in 52 episodes in high-risk hematological patients concluded that a preemptive approach may reduce empirical antifungal use without differences in twelve-week survival rates in persistently febrile neutropenic patients, but this work did not include children [71] . We rarely use preemptive therapy because of the high false positive rate of GM and Aspergillus PCR.…”
Section: Preemptive Treatmentmentioning
confidence: 99%